Gastric cancer, inflammatory bowel disease and polyautoimmunity in a 17-year-old boy: CTLA-4 deficiency successfully treated with Abatacept. Issue Volume 33:Issue S1(2021) (21st May 2021) - Angelino, Giulia; Cifaldi, Cristina; Zangari, Paola; Di Cesare, Silvia; Di Matteo, Gigliola; Chiriaco, Maria; Francalanci, Paola; Faraci, Simona; Rea, Francesca; Romeo, Erminia Francesca; Amodio, Donato; Ursu, Giorgiana Madalina; et al.
Abstract : Gut involvement is frequent in immunologic disorders, especially with inflammatory manifestations but also with cancer. In the last years, advances in functional and genetic testing have improved the diagnostic and therapeutic approach to immune dysregulation syndromes. CTLA-4 deficiency is a rare disease with variable phenotype, ranging from absence of symptoms to severe multisystem manifestations and complications. We describe a rare case of CTLA-4 deficiency in a boy with gastric cancer, very early onset inflammatory bowel disease and polyautoimmunity, the second-ever reported in the literature with the same characteristics. A 17-year-old boy was referred to Bambino Gesù Children's Hospital of Rome, a tertiary care center, for a gastric mass and a long-term history of very early onset inflammatory bowel disease, diabetes mellitus type 1, polyarthritis and psoriasis. Histology of gastric biopsies revealed the presence of neoplastic signet ring cells. Imaging staging showed localized cancer; therefore, the patient underwent subtotal gastrectomy with termino-lateral gastro-jejunal anastomosis. Immunological work up and genetic testing by next-generation sequencing panels for primary immunodeficiencies led to the diagnosis of CTLA-4 deficiency. Good disease control was obtained with the administration of Abatacept. The patient experienced an asymptomatic SARS-CoV-2 infection without any concern. Eighteen months after treatment initiation, the patient is alive and well. Immunologic and genetic testing, such as next-generation sequencing, should always be part of the diagnostic approach to patients with complex immune dysregulation syndrome, severe clinical course, poor response to treatments or cancer. The early recognition of the monogenic disease is the key for disease management and targeted therapy.